195k views
1 vote
Solve the following logarithmic equations
log(x) + log(−x) = 0

1 Answer

5 votes

Answer:

x= +i and x = -i

Explanation:

First we use the property of a sum of logarithms (the sum of two logarithms is equal to multiplying them) and we have that

log (x) + log (-x) = 0

log((x)(-x)) = 0

log (-x²) = 0

we can write this as an exponential equation. ( When you have a single logarithm on one side of the equation then you can express it as an exponential equation and solve)

-x²= 10⁰

-x²= 1

x²= -1

x= ±i

Therefore the solutions are x= +i and x = -i

User Sshine
by
4.9k points